1988
DOI: 10.1002/mrd.1120210206
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine potentiates forskolin‐induced delay of meiotic resumption by mouse denuded oocytes: Evidence for an oocyte surface site of adenosine action

Abstract: Adenosine is present in the mouse follicular fluid and has been shown to interfere with oocyte maturation in vitro. To clarify the mechanism of adenosine action on meiotic arrest, we have characterized the synergistic action of this purine with forskolin on the meiotic resumption of mouse denuded oocytes. Forskolin delays meiotic resumption by approximately 1 hour; adenosine at concentrations ranging between 30-750 microM has no significant effect. Conversely, adenosine treatment together with forskolin produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
2
17
0
1
Order By: Relevance
“…This primitive morphogenetic system illustrates the utility of adenosine as a regulatory link between cellular metabolism and cell function. Other studies have shown the ability of adenosine to regulate vascular development (Dusseau et al, 1986;Adair et al, 1989), meiotic maturation of the oocyte (Eppig et al, 1985;Salustri et al, 1988), and embryonic limb-bud outgrowth (Knudsen and Elmer, 1987). These data suggest that adenosine may mediate intercellular interactions although its role in development is not understood.…”
Section: Introductionmentioning
confidence: 95%
“…This primitive morphogenetic system illustrates the utility of adenosine as a regulatory link between cellular metabolism and cell function. Other studies have shown the ability of adenosine to regulate vascular development (Dusseau et al, 1986;Adair et al, 1989), meiotic maturation of the oocyte (Eppig et al, 1985;Salustri et al, 1988), and embryonic limb-bud outgrowth (Knudsen and Elmer, 1987). These data suggest that adenosine may mediate intercellular interactions although its role in development is not understood.…”
Section: Introductionmentioning
confidence: 95%
“…Following binding to the receptors at the cell surface, adenosine acts through the adenylate cyclase pathway. The receptors have been known to be expressed in both oocytes [32] and cumulus cells [33]. Adenosine A1 and A3 receptors have been known to activate adenylate cyclase, and conversely, A2 receptors inhibit adenylate cyclase [34].…”
Section: Discussionmentioning
confidence: 99%
“…More than 10 years ago, the purines, hypoxanthine (HX) and adenosine, were identified as components of follicular fluid that brought about meiotic arrest when added to cultures of spontaneously maturing mouse oocytes [6,7]. An inhibitory effect of these purines on spontaneous oocyte maturation has since been confirmed in numerous species, including the mouse [8][9][10][11], rat [12,13], cow [14], monkey [15], hamster [16], pig [17], and rabbit [18]. In addition, a sizable body of evidence has implicated the purine metabolic pathways as critical participants in the regulation of meiotic arrest (see [19] for review).…”
Section: Introductionmentioning
confidence: 98%